2010
DOI: 10.1002/cplx.20347
|View full text |Cite
|
Sign up to set email alerts
|

Buzzwords on their way to a tipping‐point: A view from the blogosphere

Abstract: words (i.e., neologisms) that enter the language and acquire great popularity as ' 'fashion words.' ' To date, the dynamic aspect of buzzwords has not been the subject of a rigorous scientific analysis. In this study, we analyzed the appearance of buzzwords in the blogosphere and compared their dynamics to the one of nonpopular neologisms and well-established words. It was found that the growth rate of buzzwords is exponential and higher than that of the blogosphere. Moreover, we have identified general early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 10 publications
1
14
0
2
Order By: Relevance
“…For example, according to Brown (), Democratic contender Howard Dean lost credibility as a presidential actor with his “notorious ‘scream’ speech” (86). Neuman, Nave, and Dolev () call “presidentialness” a “buzzword” or “neologism” in the English language, defined as: “The physical and mental qualities that make a person appear to be suitable for the job of United States president” (68). Anderson and Sheeler (2014) speak of presidentiality as the successful electoral attainment of the U.S. presidency.…”
Section: Operationalizing the Conceptual Factorsmentioning
confidence: 99%
“…For example, according to Brown (), Democratic contender Howard Dean lost credibility as a presidential actor with his “notorious ‘scream’ speech” (86). Neuman, Nave, and Dolev () call “presidentialness” a “buzzword” or “neologism” in the English language, defined as: “The physical and mental qualities that make a person appear to be suitable for the job of United States president” (68). Anderson and Sheeler (2014) speak of presidentiality as the successful electoral attainment of the U.S. presidency.…”
Section: Operationalizing the Conceptual Factorsmentioning
confidence: 99%
“…Although yet not as widely used as in natural systems, efforts to apply EWS to social systems are increasing (Scheffer, 2009;Haldane and May, 2011;Neuman et al, 2011;Saavedra et al, 2011; Kuehn et al, 2013;Moat et al, 2013;Barrett and Dannenberg, 2014;Kallus, 2014, ch. 12).…”
Section: Ews For Societal Tipping Points?mentioning
confidence: 99%
“…Recently, many studies have proposed that certain impending critical transitions can in principle be identified through generic signs called the early-warning signals (EWSs) regardless of their underlying details [11][12][13]. Most of the proposed EWSs are based on the increasing trend of some summary statistics, such as the rising of variance [14][15][16], autocorrelation coefficient at lag-one [R (1)] [17,18], skewness [14,19], and the Pearson correlation coefficient (ρ) [20,21]. The idea behind previous theory is that critical transitions correspond to dynamical bifurcations, especially the fold bifurcation (or saddle-node bifurcation).…”
Section: Introductionmentioning
confidence: 99%